DDB1 and Cul4A Are Required for Human Immunodeficiency Virus Type 1 Vpr-Induced G(2) Arrest - Tan, Lindi (American Society for Microbiology, 2007)
Vpr-mediated induction of G(2) cell cycle arrest has been postulated to be important for human immunodeficiency virus type 1 (HIV-1) replication, but the precise role of Vpr in this cell cycle arrest is unclear. In the present study, we have shown that HIV-1 Vpr interacts with damaged DNA binding protein 1 (DDB1) but not its partner DDB2. The interaction of Vpr with DDB1 was inhibited when DCAF1 (VprBP) expression was reduced by short interfering RNA (siRNA) treatment. The Vpr mutant (Q65R) that was defective for DCAF1 interaction also had a defect in DDB1 binding. However, Vpr binding to DDB1 was not sufficient to induce G(2) arrest. A reduction in DDB1 or DDB2 expression in the absence of Vpr also did not induce G(2) arrest. On the other hand, Vpr-induced G(2) arrest was impaired when the intracellular level of DDB1 or Cullin 4A was reduced by siRNA treatment. Furthermore, Vpr-induced G(2) arrest was largely abolished by a proteasome inhibitor. These data suggest that Vpr assembles with DDB1 through interaction with DCAF1 to form an E3 ubiquitin ligase that targets cellular substrates for proteasome-mediated degradation and G(2) arrest.